ANALISIS PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN MENGGUNAKAN METODE REGRESI LINIER (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
This research was conducted to explore and evaluate whether product quality affects customer satisfaction at the Mixue branch in Margonda. The study participants were customers who purchased ice cream or drinks at the Mixue Margonda branch. The sample consisted of 50 respondents selected through an online questionnaire distribution. The approach used was quantitative, and SPSS version 26 was used for data analysis. The validity and reliability of the research instruments were tested. Data analysis employed simple linear correlation and regression with product quality (x) and customer satisfaction (y) variables. The correlation results demonstrated a significant positive relationship between product quality and customer satisfaction. Simple linear regression showed the equation y = 3.341 + 0.746x, and partially, the product quality variable had a relevant impact on customer satisfaction. This research confirms that product quality significantly impacts customer satisfaction at the Mixue outlet, highlighting the importance of improving product quality to enhance customer satisfaction.
Keywords: analysis; customer satisfaction; linear regression; product quality